Música em Mato Grosso do Sul: territórios, povos e narrativas nas canções de Paulo Simões e parceiros (1960 – 1990) - Flávio Zancheta Faccioni (2024)
The general objective of this thesis is to observe, identify and problematize the territories, peoples, narratives and cultures in/of Mato Grosso do Sul; and the specific objectives are to reflect on the South-Mato Grosso identification processes from the songs; record the discursive formations and regularities present in the songs; and debate the history, memory and peoples in/of Mato Grosso do Sul. I start from the hypothesis that during the decades from 1960 to 1990, Paulo Simões and partners, motivated and restless by the division of Mato Grosso and creation of Mato Grosso do Sul, composed songs that enable the cultural construction south-mato-grossense. The questions that guide my analytical gesture are divided between whether the cultural construction would be situated in the historical-social moment of the division of Mato Grosso Uno and whether the songs composed in these decades are directed to a specific audience. To achieve the objectives, question the hypothesis and discuss the research questions, I link myself to the French Discourse Analysis, as well as to the studies of Geography, Anthropology, History and Music, Foucaultian archaeogenealogy as the north to perform the theoretical-methodological procedures. I divide the thesis into three parts, in Part 1 present the conditions of production and the paths of culture; in Part 2 I align the concepts and methodological procedures; finally, in Part 3 I proceed my analytical gesture. From the excavations and the destabilizations, I identified that the songs analyzed sing the territories, the peoples, the narratives and the cultures of the mesoregions of the Pantanais, Sudoeste and Centro Norte. Although one hears "culture sul-mato-grossense", I observe that there are several identification processes that constitute this definition. Keywords: Discourse; Linguistic materiality; Identification processes; Cultural construction.